2014
DOI: 10.1371/journal.pone.0095059
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Polymorphism rs3217927 of CCND2 and the Risk of Childhood Acute Lymphoblastic Leukemia in a Chinese Population

Abstract: CyclinD proteins, the ultimate recipients of mitogenic and oncogenic signals, play a crucial role in cell-cycle regulation. CyclinD2, one of the cyclinD family, is overexpressed in T-acute lymphoblastic leukemia (ALL) and B-cell chronic lymphocytic leukemia and involved in the pathogenesis of leukemias. Recent reports indicated that CCND2 polymorphisms are associated with human cancer risk, thusly we hypothesized that CCND2 gene polymorphisms may contribute to childhood ALL susceptibility. We selected the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
8
4
Order By: Relevance
“…By binding to the IGF1R, it initiates intracellular signal pathway, including PI3K-AKT pathway, a stimulator of cell growth and proliferation, and a potent inhibitor of programmed cell death. Our previous studies have demonstrated that polymorphisms in the PI3K-AKT pathway are associated with risk for childhood ALL [10,11]. There is mounting evidence that IGF1 plays an important role in neoplasia [12,13,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By binding to the IGF1R, it initiates intracellular signal pathway, including PI3K-AKT pathway, a stimulator of cell growth and proliferation, and a potent inhibitor of programmed cell death. Our previous studies have demonstrated that polymorphisms in the PI3K-AKT pathway are associated with risk for childhood ALL [10,11]. There is mounting evidence that IGF1 plays an important role in neoplasia [12,13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple GWAS identified a series of risk loci such as ARID5B, IKZF1, GATA3, CDKN2A, and BMI1-PIP4K2A [6,7,8,9], which have not been consistently identified across these GWAS but validated by meta-analyses. Our previous studies have demonstrated that polymorphisms in the PI3K-AKT pathway are associated with risk for childhood ALL [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…CCND2 (cyclin D2) and BAALC expression have prognostic relevance in leukemia and other malignancies. 58,59 In addition, we compared gene expression profiles of 5 MLL-AF4 cases, 4 MLL-AF9 cases, and 3 MLL-ENL cases with those of normal human BM CD34 1 CD38 2 HSCs isolated from 3 healthy donors. We found relative overexpression of cell surface molecules CD9, CD24, CD32, CD127, and CD180b in MLL-AF4 CD34 Figure 5A).…”
Section: Gene Expression Signatures In Mll Lics and Hscsmentioning
confidence: 99%
“…They regulated different target genes in the two processes and also regulated a few shared target genes, such as CCND2, SH3BP5 and HHEX. Multiple studies suggested that abnormal expression of CCND2 involved in the pathogenesis of leukemia 29 30 .…”
Section: Resultsmentioning
confidence: 99%